De novo small cell neuroendocrine carcinoma of the prostate with extremely elevated PSA and Gleason score 5 + 5: a case report - Tang, Yiwen; Cai, Yuyang; Jiang, Xiaofeng; Qiao, Ruoyu; Gao, Zhan (Frontiers in Oncology, 2026)
ObjectivesThe aims of this study were to report an exceptionally rare case of de novo small cell neuroendocrine carcinoma of the prostate (SCNEPC) presenting with unprecedented prostate-specific antigen (PSA) elevation and Gleason score 5 + 5, and to describe the remarkable treatment response achieved with multimodal therapy.CaseA 72-year-old man presented with PSA 982 ng/mL and extensive skeletal metastases. Prostate biopsy revealed mixed histology comprising small cell neuroendocrine carcinoma (Gleason 5 + 5 = 10) in seven cores and adenocarcinoma (Gleason 5 + 4 = 9) in three cores (T3bN1M1). The patient received six cycles of cisplatin–etoposide chemotherapy combined with goserelin and apalutamide. Post-treatment evaluation demonstrated profound biochemical response with PSA declining to 0.90 ng/mL (99.9% reduction), pro-gastrin-releasing peptide (ProGRP) decreasing to 75.7 pg/mL, and testosterone suppressed to castrate levels. Imaging confirmed substantial lesion regression with no new metastases. The patient experienced dramatic clinical improvement and remains alive with controlled disease under ongoing androgen deprivation therapy.ConclusionThis represents the first reported case of de novo SCNEPC with Gleason score 5 + 5, demonstrating that intensive multimodal therapy combining platinum-based chemotherapy with contemporary androgen receptor pathway inhibition can achieve profound and sustained responses in this aggressive variant typically associated with dismal outcomes. The substantial adenocarcinoma component may have contributed to the exceptional treatment response.